Transformações e usos do Patrimônio no Centro Histórico de São Luís (Maranhão) - ROCHA, Abigail Vale (2025)
This dissertation analyzes the transformations and uses of “heritage” in the Historic Center of São Luís, addressing its material dimensions (houses, streets, squares etc.) and social (daily interactions). The research adopted an ethnographic approach, combining field work and anthropological theory, from the narratives of residents, institutional events and speeches of local media. It was observed that the concept of “degradation” - both in the physical aspect (deterioration of the houses) and social (behaviors considered “deviant”) - occupies a central place in the discussions about the so-called “preservation” of the region. It was investigated how these narratives are reflected in the daily practices of housing, work and leisure, and how they impact the transformation of spaces. The dissertation also explored the relationship between “heritage” and popular economy, analyzing how the uses of spaces influence social representations and local ways of life in an area recognized as a World Heritage since 1997. We also analyzed the affective ties established in the exchanges between people, houses, objects and animals, and how these relations contribute to the re-meaning of heritage spaces. Thus, it was sought to deepen the understanding of daily practices in the Historic Center, considering the negotiations between the narratives of “preservation” and the demands of the inhabitants, and demonstrating how the “heritage” is constantly transformed and reinterpreted in the local context.